1989
DOI: 10.1111/j.1464-410x.1989.tb05255.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Bacillus Calmette‐Guérin Treatment for Superficial Bladder Tumours

Abstract: Intravesical instillations of Tokyo 172 strain BCG were given to 56 patients with superficial bladder cancer during the 24-month period after transurethral tumour resection as a prophylaxis against tumour recurrence. The recurrence rate of tumours was compared with that of historical controls. Results were estimated by the person-years method and there were statistically significant decreases in recurrent tumours following BCG therapy. Our results suggest that the intravesical Tokyo 172 strain BCG is effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…2 Since then, BCG has established itself as the most effective form of intravesical therapy for the prophylaxis and treatment of superficial bladder cancer. 3,4 However, several studies have suggested that the immune response cascade in the submucosa of the urinary bladder after intravesical BCG therapy is involved in the mechanism by which BCG prevents the proliferation of bladder cancer. 5,6 Previously, we noted a marked increase in the amount of urinary polymorphonuclear neutrophil leukocytes immediately after intravesical BCG instillation and indicated the involvement of a preinflammatory cytokine (granulocyte-macrophage colony-stimulating factor, GM-CSF) produced by active helper T cells, which could be induced by BCG in the submucosa of the urinary bladder.…”
Section: Introductionmentioning
confidence: 99%
“…2 Since then, BCG has established itself as the most effective form of intravesical therapy for the prophylaxis and treatment of superficial bladder cancer. 3,4 However, several studies have suggested that the immune response cascade in the submucosa of the urinary bladder after intravesical BCG therapy is involved in the mechanism by which BCG prevents the proliferation of bladder cancer. 5,6 Previously, we noted a marked increase in the amount of urinary polymorphonuclear neutrophil leukocytes immediately after intravesical BCG instillation and indicated the involvement of a preinflammatory cytokine (granulocyte-macrophage colony-stimulating factor, GM-CSF) produced by active helper T cells, which could be induced by BCG in the submucosa of the urinary bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Different strains of BCG might have dissimilar effects. The reported efficient strains included Tice, Pasteur, Armand Frappier, and Tokyo 172 [26,27], In general the response rate was between 50 and 85% and the most frequent complica tions were chemical cystitis, hematuria, fever, and liver function impairment [28,29], Taipei-NIPM BCG in--4-.U Table 4. NK cell cytotoxicity in mice spleen after receiving 6 con-;quent weekly instillations of normal saline or BCG (5 mg/ml) withut prior cauterization of bladder 6 rophage, activated T cells, and HLA-DR antigen-acti vated cells [39] and monocytes [40].…”
Section: Resultsmentioning
confidence: 99%
“…The most effective of these appeared to be BCG. Immunotherapy with BCG has been used with success, because the response rates range from 50 to 100% [2,6]. Since 1986, intravesical BCG immunotherapy has been used in our institute for prophylaxis after TUR of superficial bladder tumors with a high success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral resection (TUR) with cystoscopic and cytological follow-up is the standard therapy for superficial bladder cancer. The major problems in the management of superficial bladder cancer are high recurrence rate and malignant progression after TUR [1,2]. Since multifocal field changes may contribute to the recurrence of bladder tumors, additional treatment might be appropriate to supplement the endo- scopic resection in certain patients.…”
Section: Introductionmentioning
confidence: 99%